Recurrent hotspot mutations in HRAS Q61 and PI3K-AKT pathway genes as drivers of breast adenomyoepitheliomas - Geyer, Felipe C.; Li, Anqi; Papanastasiou, Anastasios D.; Smith, Alison; Selenica, Pier; Burke, Kathleen A.; Edelweiss, Marcia; Wen, Huei-Chi; Piscuoglio, Salvatore; Schultheis, Anne M.; Martelotto, Luciano G.; Pareja, Fresia; et al. (Nature Publishing Group, 2018)
Adenomyoepithelioma of the breast is a rare tumor characterized by epithelial-myoepithelial differentiation, of which a subset will progress to invasive or metastatic cancer. We sought to define the genomic landscape of adenomyoepitheliomas. Massively parallel sequencing revealed highly recurrent somatic mutations in HRAS and PI3K-AKT pathway-related genes. Strikingly, HRAS mutations were restricted to estrogen receptor (ER)-negative tumors, all affected codon 61, and all but one co-occurred with PIK3CA or PIK3R1 mutations. To interrogate the functional significance of HRAS Q61 mutations in adenomyoepithelial differentiation, we expressed HRASQ61R alone or in combination with PIK3CAH1047R in non-transformed ER-negative breast epithelial cells. HRASQ61R induced characteristic phenotypes of adenomyoepitheliomas such as the expression of myoepithelial markers and loss of e-cadherin, hyperactivation of AKT signaling, and transformative properties that were arrested by combination therapy with AKT and MEK inhibitors. Our results indicate that breast adenomyoepitheliomas often manifest a unique transformation program featuring HRAS activation.